2019
DOI: 10.1128/jvi.00107-19
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Colocalization of Middle East Respiratory Syndrome Coronavirus Attachment and Entry Receptors

Abstract: Middle East respiratory syndrome coronavirus (MERS-CoV) uses the S1 B domain of its spike protein to bind to dipeptidyl peptidase 4 (DPP4), its functional receptor, and its S1 A domain to bind to sialic acids. The tissue localization of DPP4 in humans, bats, camelids, pigs, and rabbits generally correlates with MERS-CoV tropism, highlighting the role of DPP4 in virus pathogenesis and transmission. However, MERS-CoV S1 A does not indiscriminately bind to all ␣2,3-sialic acids, and the species-specific binding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 63 publications
0
49
0
Order By: Relevance
“…Viral replication and tropism is mainly governed by many factors including the availability of specific viral receptors and transcription factors. It is believed that MERS-CoV utilizes the DPP-4 as main receptors and sialic acid as accessory receptors [7]. MERS-CoV infection usually starts with the attachment of the virus by its spike glycoproteins to the target cell DPP4 ligands [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Viral replication and tropism is mainly governed by many factors including the availability of specific viral receptors and transcription factors. It is believed that MERS-CoV utilizes the DPP-4 as main receptors and sialic acid as accessory receptors [7]. MERS-CoV infection usually starts with the attachment of the virus by its spike glycoproteins to the target cell DPP4 ligands [7].…”
mentioning
confidence: 99%
“…It is believed that MERS-CoV utilizes the DPP-4 as main receptors and sialic acid as accessory receptors [7]. MERS-CoV infection usually starts with the attachment of the virus by its spike glycoproteins to the target cell DPP4 ligands [7]. One study have found that DPP4 was detected on cells in the cortical apical proximal tubular epithelium and arteriolar smooth muscle of kidney of camel [8].…”
mentioning
confidence: 99%
“…S proteins of all CoVs contain both an NTD and a CTD, but different CoVs evolve to use either the NTD or CTD to bind their cognate receptor. Some CoVs, such as MERS-CoV, use their CTDs to bind protein receptors and NTDs to bind sugar moieties (45,46). One intriguing question is whether there is any cross-domain communication between the NTD and CTD during conformational changes of the S protein leading to virus entry.…”
Section: Discussionmentioning
confidence: 99%
“…However, while dromedary camels and New World camelids could transmit MERS-CoV upon contact, rabbits could hardly transmit the virus [130,143]. MERS-CoV has been shown to use α-2,3 SA as a receptor assistant, which dromedary camels but not rabbits express in the nasal epithelium [130,151,152]. Humans do not express the primary receptor DPP4 in the upper respiratory tract but transmits MERS-CoV well [153].…”
Section: Animal Models Of Mers-cov Infectionmentioning
confidence: 99%
“…It is now known that DPP4 is a functional cellular receptor for MERS-CoVs and that Vero cells express DPP4 [193]. Vero cells also express α-2,3 SA, which has been shown to assist receptor binding of MERS-CoVs [130,151,152,167]. Vero cells are well known for an impairment in the type I interferon pathways [194].…”
Section: Pandemic Potential Of Mers-covmentioning
confidence: 99%